Biopolymer From Starch And Chitosan As Bioplastic Material For Food Packaging - Umi Fathanah; Mirna Rahman Lubis; Ryan Moulana (Syiah Kuala University, 2015)
This research aims to improve economic value of cassava peel waste as raw material of bioplastic making, whose existence is still very abundant and has not been benefitted optimally. Bioplastic making is conducted by mixing starch and chitosan with gliserol as plasticizer. Bioplastic making is carried out at gelatinization temperature of 80oC. Chitosan addition is carried out at variatios of 0; 10; 20; 30; and 40 (% w). Research result indicates that mechanical property i.e. optimum value of tensile strength is obtained at value of 38.25 MPa with chitosan addition as much of 30%. The highest elongation percentage is obtained as much of 41.25% with addition of 10% chitosan. Physical property of resulted bioplastic is obtained from the best swelling test at addition of 40% chitosan i.e. 0.38%, and bioplastic density obtained is ranged from 2 – 3.33 g/ml. Analysis of functional group by using FTIR exhibits the existence of ester and carbonyl groups that indicates that resulted bioplastic could be degraded. Whereas biodegradability test on environment exhibits that bioplastic could be completely degraded in soil for 24 days.